Оценка опасности отказа резервированной системы методом ускоренного моделирования - Кузнецов, Н.Ю.; Шумская, А.А. (Проблемы управления и информатики, 2013)
Розглянуто резервовану систему, що містить відновлювані, невідновлювані та періодично контрольовані елементи. Жоден з розподілів не є експоненціальним. Запропоновано метод зваженого моделювання, який дозволяє будувати незміщені оцінки небезпеки відмови системи одночасно у декількох точках. На прикладі енергетичної системи ілюструється висока точність оцінок. A redundant system consisting of repairable, unrepairable and periodically tested components is considered. None of distributions involved is supposed to be of exponential type. A method of weighted simulation enabling to construct unbiased estimates for the hazard of failure of the system simultaneously in several points is proposed. High accuracy of estimates is demonstrated on the example of power supply system.